2010
DOI: 10.1002/syn.20876
|View full text |Cite
|
Sign up to set email alerts
|

Curcuminoids rescue long‐term potentiation impaired by amyloid peptide in rat hippocampal slices

Abstract: Curcuminoids are vital constituent of turmeric, with therapeutic potential in the treatment of Alzheimer's disease. Electrically, stimulus train-elicited plastic changes in hippocampal CA1 excitability were used as an experimental paradigm to study the effects of curcuminoid mixture and individual components on functional failure induced by Aβ peptide in vitro. Electrical stimulation was applied on Schaffer collaterals, and population spikes (PS) were recorded from stratum pyramidale. To induce long-term poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 44 publications
1
27
0
Order By: Relevance
“…Structurally speaking, site II is less flexible than site I [24], the molecular size of Bdmc makes it easier to fit into site II than Cur. Similar relationship between curcuminoids was found by Ahmed T et al that curcuminoids rescue long-term potentiation impaired by amyloid peptide in rat hippocampal slices in the order of Bdmc > Dmc > Cur [42].…”
Section: Discussionsupporting
confidence: 83%
“…Structurally speaking, site II is less flexible than site I [24], the molecular size of Bdmc makes it easier to fit into site II than Cur. Similar relationship between curcuminoids was found by Ahmed T et al that curcuminoids rescue long-term potentiation impaired by amyloid peptide in rat hippocampal slices in the order of Bdmc > Dmc > Cur [42].…”
Section: Discussionsupporting
confidence: 83%
“…27,28 Curcuminoids can restore the capacity for plastic changes in CA1 excitability that is impaired by exposure to the Aβ peptide and rescue the reduction in long-term potentiation (LTP) in Aβ-peptideexposed hippocampal CA1 neurons. 29 We have previously reported that curcumin improves the spatial learning and memory abilities of APPswe/ PS1dE9 double transgenic mice. 23 Therefore, we sought to determine whether curcumin affects the pathology of AD via the synapses.…”
Section: Discussionmentioning
confidence: 95%
“…Curcumin can reduce amyloid in vivo in transgenic AD models and remove existing plaques [248-251]. Curcumin also reduces Aβ-mediated blockade of long-term potentiation (LTP) [252], a likely electrophysiological correlate of learning and memory. Trials of curcumin in AD patients have been explored [253] and further studies are ongoing.…”
Section: Discussionmentioning
confidence: 99%